The European semester and EU social policy - Copeland, P; Daly, M (Wiley, 2018)
The focus of this article is on EU social policy-making since 2010 in the context of new governance arrangements and changing policy orientations and politics under the European Semester and Europe 2020. Analysis of these developments can tell us something very important about the consensus around social policy in the EU, and in the member states more broadly, given the potentially important role to be played by social policy in adjusting to the financial crisis. The last five years have been especially momentous in an EU context. The European Semester was introduced in 2011, inaugurating a significant new annual governance cycle to monitor and enforce compliance with stringent budgetary and structural reforms (European Commission, 2010). A key part of the Semester - and the strongest mechanism available to the EU institutions to influence social policy developments at member state level - is the issuing of Country Specific Recommendations (CSRs) to member states in areas of perceived weakness. Europe 2020, the ten-year programme of economic, employment and social policy goals and priorities of the EU, introduced ten integrated guidelines to be taken forward by five headline targets and seven flagship initiatives. Social policy has an explicit place in Europe 2020, especially in terms of poverty and social inclusion, employment, pensions, health and social care. For example, one of the five targets aims to lift some 20 million people out of poverty and social exclusion by 2020.